2014
DOI: 10.3892/mmr.2014.2988
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of isoproterenol-induced cardiac hypertrophy and modulation of myocardial connexin43 by a KATP channel agonist

Abstract: Abstract. Cardiac hypertrophy is a compensatory mechanism that occurs in conjunction with cardiovascular diseases. Although hypertrophy of the myocardium provides certain benefits during the early stages of cardiovascular disease, prolonged hypertrophy is potentially harmful to the heart and can result in arrhythmia and heart failure. The aim of this study was to investigate whether an ATP-sensitive K + (K ATP ) channel agonist was capable of reducing isoproterenol (Iso)-induced cardiac hypertrophy and modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…Metias et al [17] reported similar changes in Cx-43 in ISO-induced MI. Also, Sun et al [53] concluded that the reduction and redistribution of myocardial Cx-43 might be mediated by ATP-sensitive potassium channels through preserving protein kinase C-dependent connexion-43 level after MI. Disruption of myocardial Cx-43 in the present study might be explained by enhanced oxidative stress in the heart tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Metias et al [17] reported similar changes in Cx-43 in ISO-induced MI. Also, Sun et al [53] concluded that the reduction and redistribution of myocardial Cx-43 might be mediated by ATP-sensitive potassium channels through preserving protein kinase C-dependent connexion-43 level after MI. Disruption of myocardial Cx-43 in the present study might be explained by enhanced oxidative stress in the heart tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases of cardiac diseases, electrical remodeling, such as alterations in ion channels or Ca 2+ cycling, precedes the observed depression of mechanical performance, suggesting that amelioration of electrical remodeling might be an effective therapeutic strategy against HF (Houser and Margulies, 2003; Mueller et al, 2011). K ATP is reportedly involved in ventricular remodeling, and K ATP channel agonists exert beneficial effects on cardiac structural remodeling and dysfunction (Lee et al, 2008; Sun et al, 2015). I K1 and K ATP channels are both members of inward rectifier potassium (Kir) channel family and are respectively constituted by Kir2.x and Kir6.x subunits (Hibino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of K ATP channel has also been identified to attenuate the degree of myocardial hypertrophy by modulating the expression level and spatial distribution of Cx43 [42]. Our previous study investigated the effect of STV on sarc-and mitoK ATP channels and showed that STV could sensitize these K ATP channels in a ROS dependent manner [25].…”
Section: Multiple Consensus Phosphorylation Sites For Pka and Pkc Havmentioning
confidence: 97%